Migration pattern and mortality of ethnic German migrants from the former Soviet Union: a cohort study in Germany - Kaucher, Simone; Deckert, Andreas; Becher, Heiko; Winkler, Volker (BMJ open, 2017)
Objective We aimed to investigate all-cause and cause-specific mortality among ethnic German migrants from the former Soviet Union by different immigration periods to describe associations with migration pattern and mortality. Design: We used pooled data from three retrospective cohort studies in Germany. Participants: Ethnic German migrants from the former Soviet Union (called resettlers), who immigrated to Germany since 1990 to the federal states North Rhine-Westphalia and Saarland and to the region of Augsburg (n=59 390). Outcome: All-cause and cause-specific mortality among resettlers in comparison to the general German population, separated by immigration period. Methods: Immigration periods were defined following legislative changes in German immigration policy (1990-1992, 1993-1995, 1996+). Resettlers’ characteristics were described accordingly. To investigate mortality differences by immigration period, we calculated age-standardised mortality rates (ASRs) and standardised mortality ratios (SMRs) of resettlers in comparison to the general German population. Additionally, we modelled sex-specific ASRs with Poisson regression, using age, year and immigration period as independent variables. Results: The composition of resettlers differed by immigration period. Since 1993, the percentage of resettlers from the Russian Federation and non-German spouses increased. Higher all-cause mortality was found among resettlers who immigrated in 1996 and after (ASR 628.1, 95% CI 595.3 to 660.8), compared with resettlers who immigrated before 1993 (ASR 561.8, 95% CI 537.2 to 586.4). SMR analysis showed higher all-cause mortality among resettler men from the last immigration period compared with German men (SMR 1.11, 95% CI 1.04 to 1.19), whereas resettlers who immigrated earlier showed lower all-cause mortality. Results from Poisson regression, adjusted for age and year, corroborated those findings. Conclusions: Mortality differences by immigration period suggest different risk-factor patterns and possibly deteriorated integration opportunities. Health policy should guard the consequences of immigration law alterations with respect to changing compositions of migrant groups and their health status.
Gesehen am 06.04.2018